Enhancing Customer Engagement through Marketing 5.0: An Empirical Analysis - K, Santhosh Kumar (New Perspective: Journal of Business and Economics, 2024)
This study explores the impact of Marketing 5.0 techniques—Artificial Intelligence and Machine Learning (AIML), Big Data Analytics (BDA), Internet of Things (IoT), Augmented Reality and Virtual Reality (ARVR), Blockchain Technology (BT), and Voice Search Optimization (VSO)—on customer engagement (CE). The research employs a regression model with a sample of 250 respondents to examine the correlations and significance between these technologies and CE. The analysis reveals that AIML, BT, and ARVR significantly enhance CE, with AIML and BT showing the strongest positive correlations. Conversely, VSO is associated with a negative impact on CE. The regression model demonstrates an adjusted R-squared value of 0.489, indicating that these predictors explain a substantial portion of the variability in CE. ANOVA results confirm the model's statistical significance, emphasizing the importance of AIML, BT, and ARVR in improving customer interaction and brand involvement. The findings highlight the transformative potential of Marketing 5.0 technologies in delivering personalized and immersive experiences that drive customer loyalty and business growth in a competitive digital landscape. Organizations should strategically integrate AIML, BT, and ARVR into their marketing efforts to enhance customer engagement and gain a competitive edge.